Integrated approach to recognize square-ROI in breast cancer augmentation - Rechard Lee (2014)
The ultimate goal of an AR system is to create a mixed-digital environment such that the computer–generated objects mixed into the real-world environment as one of its entities. Thus, the object must be visually registered in every point the user sees. To maintain the user’s illusion that the virtual objects are part of the real world requires a consistent registration of the virtual world with the real world, and this stringent requirement of the system is one of the challenges in developing an AR system (Klein, 2006; Xu et al., 2003; Azuma, 1997).